Differential Gene Expression Analysis in Polygonum minus Leaf Upon 24 hours of Methyl Jasmonate Elicitation - Rahnamaie-Tajadod, Reyhaneh; Loke, Kok-Keong; Goh, Hoe-Han; Mohd Noor, Normah (Frontiers in Plant Science, 2017)
Polygonum minus is an herbal plant that grows in Southeast Asian countries and traditionally used as medicine. This plant produces diverse secondary metabolites such as phenolic compounds and their derivatives, which are known to have roles in plant abiotic and biotic stress responses. Methyl jasmonate (MeJA) is a plant signaling molecule that triggers transcriptional reprogramming in secondary metabolism and activation of defense responses against many biotic and abiotic stresses. However, the effect of MeJA elicitation on the genome-wide expression profile in the leaf tissue of P. minus has not been well-studied due to the limited genetic information. Hence, we performed Illumina paired-end RNA-seq for de novo reconstruction of P. minus leaf transcriptome to identify differentially expressed genes (DEGs) in response to MeJA elicitation. A total of 182,111 unique transcripts (UTs) were obtained by de novo assembly of 191.57 million paired-end clean reads using Trinity analysis pipeline. A total of 2,374 UTs were identified to be significantly up-/down-regulated 24 h after MeJA treatment. These UTs comprising many genes related to plant secondary metabolite biosynthesis, defense and stress responses. To validate our sequencing results, we analyzed the expression of twenty one selected DEGs by quantitative real-time PCR and found a good correlation between the two analyses. The single time-point analysis in this work not only provides a useful genomic resource for P. minus but also gives insights on molecular mechanisms of stress responses in P. minus.